A review on phenomenological model subtleties for defect assessment in friction stir welding - Das, Debtanay; Bag, Swarup; Pal, Sukhomay; De, Amitava (Journal of manufacturing processes, 2024)
Friction stir welding (FSW) is in existence for well over three decades. Started primarily with the joining of aluminium alloys, FSW is gradually engaged for other alloys and also examined for additive manufacturing. The conventional experimental and theoretical studies on FSW focus on finding process parameters and tool geometry for producing a weld joint and ignores the insight for the evolution of defects. An appropriate comprehension of the mechanistic models to realize the underlying phenomena for the evolution of defects and assess their susceptibility to occur is required to enhance the application of FSW process. We present here a comprehensive review of the mechanistic models and, the constitutive and empirical relations with a focus on their substantive use for understanding the evolution of defects in FSW. Several associated factors such as tool-material interaction, computational complexity and accuracy, and the utility of commercial software are examined to present the subject. A thoughtful understanding about the mechanism of surface and volumetric defects is targeted through phenomenological behaviour of the process. We believe that this review work will provide a framework to help produce defect-free welds in FSW and allied solid-state joining processes.